Addition of hydroxyapatite from mangrove crab (Scylla serrata) shell powder to the cementation strength of glass ionomer cement: Penambahan hidroksiapatit dari serbuk cangkang kepiting bakau (Scylla serrata) terhadap kekuatan sementasi glass ionomer cement - Anisah Nabilah Ferry; Mohammad Dharma Utama; Eri Hendra Jubhari (Makassar Dental Journal, 2024)
Hydroxyapatite (HA) participates in the chemical changes that occur during the initial hardening of cement. Calcium ions can be released from the surface of HA, which acts as additional calcium for the hardening reaction of glass ionomer cement (GIC). HA increases the density of the GIC because HA fills the empty spaces between the glass particles in the GIC. One source of cal-cium that can be obtained in the synthesis of HA is crab shells. The utilisation of crab is still limited to its meat for food purposes, while the shell is discarded. Crab shell waste can cause air and soil pollution. Mangrove crab (Scylla serrata) shell waste contains high calcium compounds (CaCO3), which is 53-78% of the dry shell weight. This high calcium content can be used as HA ma-terial. This literature review discusses the synthesis of HA which can be done by various methods, including precipitation, sol-gel, hydrothermal, and wet deposition methods. Different synthesis processes will certainly produce different HA powders. It is conclu-ded that calcium compounds found in crab shells can be an additional ingredient in HA for the strength of GIC cementation.